Analisis Faktor-Faktor yang Mempengaruhi Penyerapan Tenaga Kerja di Kota Mataram Tahun 2011-2024 - Titin Wahyuni; Gusti Ayu Arini; Ali Akbar Hidayat (Economic Reviews Journal, 2026)
This study aims to analyze the influence of City Minimum Wage, Gross Regional Domestic Product and Investment on labor absorption in Mataram City in 2011-2024. This study uses quantitative research with an associative approach. The research data uses secondary data obtained from the Central Statistics Agency (BPS) of Mataram City, the Central Statistics Agency (BPS) of West Nusa Tenggara, the Investment and One-Stop Integrated Service Agency (DPMPTS) of Mataram City and the Manpower and Transmigration Agency. Data analysis was carried out using multiple linear regression through the Eviews 12 application. The results of this study indicate that the City Minimum Wage (UMK) has a positive and significant effect on labor absorption in Mataram City. Meanwhile, Gross Regional Domestic Product and Domestic Investment have a negative but insignificant effect on labor absorption in Mataram City. Simultaneously, the variables of City Minimum Wage, Gross Regional Domestic Product and Domestic Investment have a significant effect on labor absorption in Mataram City in 2011-2024.